2017
DOI: 10.1002/anie.201706570
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis‐Guided Hybrid Neutrophil Micromotors for Targeted Drug Transport

Abstract: Engineering self-propelled micromotors with good biocompatibility and biodegradability for actively seeking disease sites and targeted drug transport remains a huge challenge. In this study, neutrophils with intrinsic chemotaxis capability were transformed into self-guided hybrid micromotors by integrating mesoporous silica nanoparticles (MSNs) with high loading capability. To ensure the compatibility of neutrophil cells with drug-loaded MSNs, bacteria membranes derived from E. coli were coated on MSNs in adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 44 publications
0
157
0
1
Order By: Relevance
“…[9] Ferrite coatings were also incorporated in magnetically propelled helices for prolonged navigation in blood. [11] Then ative fluorescence of Spirulina microalgae was exploited for the construction of magnetic micromotors for bioimaging applications. [11] Then ative fluorescence of Spirulina microalgae was exploited for the construction of magnetic micromotors for bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Ferrite coatings were also incorporated in magnetically propelled helices for prolonged navigation in blood. [11] Then ative fluorescence of Spirulina microalgae was exploited for the construction of magnetic micromotors for bioimaging applications. [11] Then ative fluorescence of Spirulina microalgae was exploited for the construction of magnetic micromotors for bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…The similar trajectories have been reported by previous research which showed a chemotaxis behavior of micromotors. [ 36 ] Brownian motion was observed for functionalized particles with nontriggered cells (Figure S9, Supporting Information). In a real periodontal pocket, the concentration of H 2 O 2 is expected to be higher than the experimental condition because there exist much more immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…As stated in their cell-killing results, DOX-loaded cells significantly inhibited the proliferation of tumor cells compared with unloaded cells. Shao et al developed a hybrid neutrophil micromotor system which was guided along the chemoattractant gradients secreted by Escherichia coli for targeted drug transport ( Figure 3B & Table 2) [79]. In their research, DOX was embedded within mesoporous silica nanoparticles and then taken up by the neutrophils.…”
Section: Cells/microorganisms As Drug Carriersmentioning
confidence: 99%